Respon Guru Terhadap Modul Bioteknologi Proses Pembuatan Tempoyak Berbasis Kearifan Lokal Jambi - Arum Zaharani; Fitri Arsih (LPPM Universitas Cipta Mandiri, 2024)
Tempoyak is a traditional food made from fermented durian flesh which is popular in Sumatra and Malaysia, including Jambi Province. Due to the abundance of durian fruit in Jambi and the majority of Jambi people who used to be migrants, the processing of durian fruit into tempoyak is done to maintain its freshness and make it a traditional food that has been passed down from generation to generation. The local wisdom of making tempoyak is passed down through word of mouth and is part of a culture that is formed naturally and based on the customs and advice of ancestors. Integrating local wisdom in learning, especially in science, is important to increase the relevance and contextualization of learning. This research aims to determine teachers' responses to the use of the biotechnology module for the process of making tempoyak based on Jambi local wisdom. The method used in this research is descriptive qualitative method. The research results showed that teachers responded positively to this module because it was interesting, easy to understand, and increased students' curiosity and knowledge about local wisdom. This module also inspires teachers to innovate in learning and helps combine various types of student intelligence. It is recommended that schools be more proactive in integrating local wisdom into the curriculum and providing special training to teachers. Collaboration with local communities and further research are also needed to increase the effectiveness of this module in learning.